Distribution Of Property With Women Career Halal Business Actors Perspective Muslimat Nahdlatul Ulama And Aisiyah Muham: PEMBAGIAN HARTA BERSAMA PEREMPUAN KARIR PELAKU USAHA HALAL PRESPEKTIF MUSLIMAT NAHDLATUL ULAMA DAN AISIYAH MUHAMMADIYAH - Jannah, Roudatul; Rudi Hermawan, Adiyono; Hermawan, Rudi (Al Yasini : Jurnal Keislaman, Sosial, hukum dan Pendidikan, 2023)
Indonesian Positive Law stipulates that part of joint property is the wife's right and the other part is the husband's right in the event of a divorce. This provision is based on the husband's responsibility to earn a living, while the wife's job is to take care of the household and support her husband. However, the division of responsibilities as stated in the law has shifted. Nowadays, some wives not only act as housewives, but also work to earn a living or often even become the backbone of the family. The aim of this research is to find out about the Sharing of Assets with Women Careers of Halal Business Actors Muslimat Nahdlatul Ulama and Aisiyah Muhammadiyah Perspectives. This writing uses qualitative methods. The data collection techniques used were interviews, observation and documentation. The data obtained was then reduced to data, then presented the data and concluded conclusions to find out the distribution of assets with career women who are business actors from a halal perspective Muslimat Nahlatul Ulama and Aisiyah Muhammadiyah. Keywoards: Shared Property, Career Women, NU and Aisiyah Muslims